Molecular cloning and expression analysis of mytilin-like antimicrobial peptides from Asian green mussel Perna viridis. Issue 121 (February 2022) - Zeng, Zhiyong; Wang, Yuting; Anwar, Muhammad; Hu, Zhangli; Wang, Chaogang; Lou, Sulin; Li, Hui
Abstract: Mytilin is one of the most important CS-αβ peptides involved in innate immune response in Mytilidae. In this study, we successfully identified four mytilin-like antimicrobial peptides (pernalins) from Asian green mussel Perna viridis by aligning the P. viridis transcriptome with 186 mytilins and myticins related sequences collected from the transcriptome data of six Mytilus species. Analysis on gene structure showed that pernalin genes had high conservation with mytilin B of Mediterranean mussel Mytilus galloprovincialis . Interestingly, all pernalin genes have a similar tissue expression feature, evidenced by the highest transcription level observed in the hemocytes and followed by the mantle. The lowest transcription level was observed in the foot and gills. qRT-PCR analysis showed that all pernalin genes were significantly down-regulated at each time points from 3 h to 48 h after Vibrio parahaemolyticus infection, suggesting their timely immune responses after bacterial infection. Graphical abstract: Image 1 Highlights: Four novel mytilin-like antimicrobial peptides have identified and characterized from Asian green mussel Perna viridis. Mytilin-like in P. viridis possess conserved cysteine patterns. Mytilin-like are ubiquitously expressed in P. viridis Mytilin-like in hemocytes is down-regulated by Vibrio parahaemolyticus challenge.